Chasing the European Dream: Unaccompanied African Youths’ Educational Experience in a Canary Islands’ Reception Centre and Beyond - Valérie Auger-Voyer; Martha Montero-Sieburth; Lidia Cabrera Perez (Education Policy Analysis Archives, 2014)
In the last two decades, Spain’s Canary Islands have received thousands of undocumented migrants arriving by boat from the coasts of North and West Africa. The sharp increase of unaccompanied minors has presented a particular challenge, as these minors fall under the State’s protection system and are entitled to an education and other rights, once in Spain. What economic and socio-cultural factors push these youth to seek a better life whilst endangering their own? What educational opportunities are available to them in Spain and how can these propel them into secure living situations? What can be said about their integration prospects?